Knife : meditations after an attempted murder - Rushdie, Salman (Penguin Random House India, 2024)
From internationally renowned writer and Booker Prize winner Salman Rushdie, a searing, deeply personal account of enduring--and surviving--an attempt on his life thirty years after the fatwa that was ordered against him. Speaking out for the first time, and in unforgettable detail, about the traumatic events of August 12, 2022, Salman Rushdie answers violence with art, and reminds us of the power of words to make sense of the unthinkable. Knife is a gripping, intimate, and ultimately life-affirming meditation on life, loss, love, art--and finding the strength to stand up again.